Mengamati Perkembangan Anak Kelas 2 SMP Melalui Wawancara Langsung - Ramadhan Lubis; Muhammad Fikri Rahmadiansyah; Desi Astira; Ghina Tsuraya Aqila; Najmi Munawiroh Dalimunthe; Syaria Nailah Irawan (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
Growth is the process of increasing measurements in a person's body, while development is a process of development both psychologically and emotionally. Growth and development of several phases such as the child phase, the adolescent phase, and the phase towards adulthood. Children who are in junior high school are included in the adolescent phase. The category of adolescents is children aged 13-16 years, generally in this condition a person experiences rapid growth and development physically and psychologically. This study aims to examine the development of a second grade junior high school student through direct interaction between parents and children. Direct interaction is an important means to deeply understand the child's learning conditions including social and emotional family environmental factors that influence the development and growth process. The research method used is qualitative with data collection through in-depth interview observations with parents and children and documentation of children's activities.